Isolating the subject: cholera, control and sanitary discourse in the Istanbul International Sanitary Conference of 1866 - Kılınç, Handan. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
This study aims at studying the process of Istanbul International Sanitary Conference of 1866, politic structure of the conference and the condition of the Ottoman Empire through this process. The third international sanitary conference, which was gathered in Istanbul, only dealt with cholera disease. The main goal of the Istanbul International Sanitary Conference was to prevent the spread of cholera epidemic from Hejaz to Europe. The conference approved that the origin of cholera was India and the disease was transported by Indian pilgrims to Hejaz in hajj period and then western pilgrims spread it from Hejaz to Europe. In this case, European delegates focused on the sanitary condition of the Ottoman Empire. For this reason, the conference decided that restrictive sanitary measures and quarantine methods should be performed by the Ottoman Empire in Hejaz. Consequently, in the Istanbul International Sanitary Conference, European delegations used modern sanitary knowledge and measures as a political tool in order to give priority to benefits of Europe and to control some districts like Hejaz and Egypt. Thus, the sanitary measures approved by the conference were based on isolation, exclusion in order to segregate "diseased Eastern populations" from the West.
Keywords: Medicine -- Turkey -- History.; Cholera -- Hejaz -- History.; Public health administration -- Turkey -- History.